Reading Autobiographical Comics: A Framework for Educational Settings - Oppolzer, Markus (Anglo-amerikanische Studien / Anglo-American Studies, 2020)
This book updates reader-response criticism as the foundation of aesthetic reading in the classroom by bringing it in line with cognitive theories in literary studies and linguistics. With the help of Gilles Fauconnier and Mark Turner's conceptual integration theory, which shares a surprising number of correspondences with Wolfgang Iser's The Act of Reading, it is possible to flesh out the latter's model of narrative meaning-making. In turn, this allows for a consistent reader-response approach to the medium of comics and auto/biography as one of its dominant genres. The fragmentation of comics narratives, but also of human lives and identities, requires such a theory that can explain how different perspectives and experiences can be blended into an experiential whole.